2016
DOI: 10.3126/jnbs.v9i1.14590
|View full text |Cite
|
Sign up to set email alerts
|

Green HRM: Goal Attainment through Environmental Sustainability

Abstract: The green Human Resources Management has emerged from companies engaging in practices related to protection of environment and maintaining ecological balance. The slogan is earning profit through environmental sustainability. This paper proposes the development of a model of green human resource management by reviewing the literature on human resource aspects of environmental management. The study followed archival method of literature review. The literature has been classified on the basis of entry to exit pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…The core ideology behind green HRM is to transform not only the activities but also the workforce into green workforce as well. This as a whole refers to ways laws, policies and practices are designed to make employees behave with greener approach that benefits the nature, conservation of natural resources and societal preferences (Uddin & Islam, 2015).…”
Section: Green Hrmmentioning
confidence: 99%
“…The core ideology behind green HRM is to transform not only the activities but also the workforce into green workforce as well. This as a whole refers to ways laws, policies and practices are designed to make employees behave with greener approach that benefits the nature, conservation of natural resources and societal preferences (Uddin & Islam, 2015).…”
Section: Green Hrmmentioning
confidence: 99%
“…While Uddin and İslam [31] and Ahmad [26] classiied GHRM functions under ive categories as green recruitment, green…”
Section: Gaining a Competitivementioning
confidence: 99%
“…Green Employee Participation: EM can be achieved through proper employee involvement and employee participation [14]. The use of employee participation in EM has been noted to help prevent pollution at workplaces [36]. Researchers have found that employees' green involvement is crucial in improving the performance of EM systems, such as reducing waste and pollution in workplaces and making full use of resources.…”
Section: Pmasmentioning
confidence: 99%